2010
DOI: 10.1097/jto.0b013e3181dca330
|View full text |Cite
|
Sign up to set email alerts
|

Reported Outcome Factors for Pulmonary Resection in Metastatic Colorectal Cancer

Abstract: Pulmonary resection of metastatic colorectal cancer is widely practiced in surgical oncology. However, only a highly selected subset of patients is eligible for resection, and the average recurrence rate is still high. We reviewed the recent literature on pulmonary metastasectomy for colorectal cancer and tried to address the issue of patient selection based on prognostic parameters associated with long-term survival. No randomized phase III trials are available, and data for this review were retrieved only fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 37 publications
6
76
0
9
Order By: Relevance
“…Previous studies including our series show the prognostic significance of hilar and/or mediastinal lymph node involvement (4,7,(9)(10)(11). Even if the role of mediastinal systematic nodal dissection remains unclear (12), our results and the bulk of previous literature supported the lymph node sampling practice.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Previous studies including our series show the prognostic significance of hilar and/or mediastinal lymph node involvement (4,7,(9)(10)(11). Even if the role of mediastinal systematic nodal dissection remains unclear (12), our results and the bulk of previous literature supported the lymph node sampling practice.…”
Section: Discussionsupporting
confidence: 79%
“…Nonetheless, there is no definite agreement on the value of its prognostic role: the majority of authors failed to confirm a correlation between primary tumor stage and survival (4,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though they were well described, these criteria were questioned by some authors, as discussed in the review by Pfannschmidt et al [3]. For example, the number of lung metastases were reported to be a prognostic factor by two authors, although it was reported to have no influence in 12 other studies.…”
mentioning
confidence: 87%
“…Impact of cyclooxygenase-2 and prostaglandin-E2 expression on clinical outcome after pulmonary metastasectomy carefully selected patients 5-year survival rates of 40-68% are reported (7). Commonly accepted inclusion criteria for pulmonary metastasectomy (PM) are: (I) controlled primary tumor; (II) complete resection of all metastatic lesions; (III) exclusion of disseminated, extrathoracic disease; and (IV) an adequate performance status (8).…”
Section: Original Articlementioning
confidence: 99%